Compartmentation and localization of bioactive metabolites in different organs of Allium roylei. Issue 7 (3rd July 2014) - Abdelrahman, Mostafa; Hirata, Sho; Ito, Shin-ichi; Yamauchi, Naoki; Shigyo, Masayoshi
Abstract: To investigate the involvement of Allium roylei metabolites in the plant's defenses, a comprehensive analysis of the content of cysteine sulfoxides, flavonols, polyphenols, ascorbic acid, and saponins was carried out in the various organs of this species. Metabolomics high performance liquid chromatography (HPLC), spectral-based analysis, and histochemcial studies have given important insight to the validity of saponins as a key component involved in plant protection. The root-basal stem, bulb, and leaf extracts exhibited 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity with inhibition concentration (IC50 ) ranging from 0.649 to 0.757 mg/mL. The antimicrobial properties of the saponin and flavonoid crude extracts were evaluated. The saponin extracts demonstrated significant antifungal activity depending on the applied concentration, and the growth inhibition rate of the tested fungal pathogens ranged from 1.07 to 47.76%. No appreciable antibacterial activity was recorded in the same sample. Graphical abstract: : A comprehensive phytochemical analysis in the various organs of A. roylei was carried out . Saponin was the key component involved in plant protection against pathogen.